Mapping the Spatial Linkages in the Ginger Supply Chain of Bandung Regency: Analyzing Structure and Performance - Aisyah, Hadian Resky; Muta'ali, Lutfhi; Kurniawan, Andri (Indonesian Journal Publisher, 2024)
Bandung Regency has considerable potential for ginger production. However, weak supply chain management was linked to the limited involvement of farmers in the value chain. This study aimed to analyze the ginger supply chain in Bandung Regency using a descriptive method. The supply chain structure was evaluated using the FSCN framework, while the spatial flow of ginger was mapped using ArcMap. The performance of the supply chain was measured by calculating marketing margins and farmers' share. The results indicated that the ginger supply chain operated through three main channels, with collectors playing a dominant role. Spatial analysis revealed integration between marketing channels and distribution volumes. The smallest marketing margins were found in channel 3, with Rp—2,500 for Ginger Elephant Chinese and Rp 3,500 for Ginger Paris/Emprit. Similarly, the highest farmer's share was also observed in channel 3, with 85.29% for ginger elephant China and 79.41% for ginger paris/emprit. This highlighted that channel 3 provided the most favourable returns for farmers.